Corrosion Characteristics of Anchor Cables in Electrolytic Corrosion Test and the Applicability of the Test Method in Study of Anchor Cable Corrosion - Tao Yin; Xingsong Sun; Yujie Wang; Yufei Zhao; Shuangjing Wang; Lipeng Liu; Hongjie Chen (Advances in Civil Engineering)
The selection of corrosion test method in the corrosion study of the prestressed anchors is an important issue. In this paper, the corrosion test of anchors was conducted with electrolytic corrosion test method. The corrosion characteristics of the anchor cables were examined. The effects of sodium chloride solution concentration, current, test time, and prestress level on corrosion were studied. The applicability of electrolytic corrosion method in anchor cable corrosion study is discussed subsequently. The results show that the corrosion of the anchor appears to be uniform corrosion. With the corrosion of the anchor, the central wire of the cable was basically not corroded, and the cross-sectional shape of the outer wire changes from a round to fan shape. The sodium chloride concentration and prestress level have no obvious effects on the corrosion of the anchor. The variation of test time does not affect the difference between the measured and theoretical calculated results, while a proper current in the electrolysis test may help reduce the difference. The measured corrosion rate fluctuates from −4% to 10% and tends to be higher compared with calculated results based on Faraday’s law. The study indicates that the electrolytic corrosion test is applicable in the anchor corrosion study.